A Rare Case of Hemoptysis: Intrapulmonary Cavitary Lesion Appearing as a Thoracic Endometriosis. (30th August 2012) - Celik, Ali; Aydın, Ertan; Yazıcı, Ulku; Agackıran, Yetkin; Karaoglanoglu, Nurettin
Abstract : Pulmonary endometriosis is a rarely seen disease of the lung. On computed tomography, a cavitary lesion of 15 × 26 in size was detected in the lung parenchyma of a 38-year-old female patient who was examined due to hemoptysis. The pathologic result of the surgically excised cavitary lesion was reported as pulmonary endometriosis.